The Influence of Green Marketing on Consumer Purchase Decisions Through Green Brand Image in Minimarkets in Jakarta - Edi Wahyu Wibowo; Syamsurizal; Dingot Hamonangan Sitanggang (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Increasing public awareness of environmental issues has encouraged retail companies to implement green marketing strategies to create competitive advantages while supporting sustainable development. The minimarket industry in Jakarta faces challenges in meeting consumer demands for environmentally responsible products and services. This study aims to examine the influence of green marketing on consumer purchase decisions with green brand image as a mediating variable. This research employs a quantitative approach using a survey method involving 250 minimarket consumers in Jakarta selected through purposive sampling. Data are collected using a five-point Likert questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The expected findings indicate that green marketing positively affects green brand image and purchase decisions. Furthermore, green brand image is expected to mediate the relationship between green marketing and purchase decisions. This study contributes to the development of green marketing literature and provides managerial implications for minimarket businesses in implementing sustainable marketing strategies.